Open educational resources (OER) [electronic resource] - UNESCO (Paris Unesco, 2019)
Quoted from the homepage: This page lists all the documents related to the Open Educational Resources (OER).
mixed.
online.
Keywords: Electronic information resources; Internet research; Internet in higher education; Open learning; Education, Higher; Electronic books; College teaching -- Electronic portfolios. .; College teaching -- Aids and devices -- Electronic portfolios. .; Universities and colleges -- Curricula -- Aids and devices -- Electronic portfolios. .; Web-based instruction; Education, Higher -- Web-based instruction; Universities and colleges -- Web-based instruction